2000
DOI: 10.1099/0022-1317-81-5-1321
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccination with both the haemagglutinin and fusion proteins but not the nucleocapsid protein protects against experimental measles virus infection

Abstract: Plasmids that expressed the nucleocapsid, haemagglutinin and fusion proteins of measles virus (MV) were used to immunize cotton rats (Sigmodon hispidus) against intranasal MV infection. After immunization with all three plasmids, T cell responses and MV-specific antibodies were induced. A reduction in virus titre was observed in lung tissue from animals immunized with plasmids expressing the viral glycoproteins. Histologically, however, a moderate peribronchitis was observed after immunization with the plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Such a prime-boost strategy could protect very young infants in developing countries against measles infection during the first year of life. 4 Ags have been pursued as promising measles vaccine candidates. Several studies have shown a degree of protective efficacy using a variety of DNA plasmids encoding MV hemagglutinin and fusion glycoproteins in cotton rats (3,4) and rhesus macaques (5)(6)(7).…”
mentioning
confidence: 99%
“…Such a prime-boost strategy could protect very young infants in developing countries against measles infection during the first year of life. 4 Ags have been pursued as promising measles vaccine candidates. Several studies have shown a degree of protective efficacy using a variety of DNA plasmids encoding MV hemagglutinin and fusion glycoproteins in cotton rats (3,4) and rhesus macaques (5)(6)(7).…”
mentioning
confidence: 99%
“…has been studied in different animal model and for different parasites, such as, Schistosoma (Mohamed et al 1998), Plasmodium (Grifantini et al 1998), Leishmania (Xu et al 1995) and Mycobacterium (Morris et al 2000); virus, as rabies (Lodmell et al 1998), herpes (Sin et al 2000), hepatitis C (Arichi et al 2000), influenza (Dégano et al 2000, Johnson et al 2000, dengue (Raviprakash et al 2000), measles (Schlereth et al 2000), cytomegalovirus (Morello et al 2000); as well as for melanoma (Xiang et al 2000), and immune diseases, such as encefalomielitis (Weissert et al 2000).…”
mentioning
confidence: 99%
“…fection (29). On the other hand, neutralizing antibodies against the hemagglutinin protein are protective against infection.…”
Section: Immunization With Cd4 T-cell Epitope From the Hemagglutinin mentioning
confidence: 99%
“…For DNA vaccination plasmids pSC-N (nucleocapsid protein), pCG-F1 (fusion protein), or pCG-H5 (hemagglutinin) (29) were used. Plasmid DNA was purified using a plasmid Maxi kit (QIAGEN, Hilden, Germany).…”
Section: Animalsmentioning
confidence: 99%